Susceptibilities of Eikenella corrodens, Prevotella intermedia, and Prevotella nigrescens Clinical Isolates to Amoxicillin and Tetracycline - Luong, N. (American Society for Microbiology, 2001)
The AB Biodisk Etest showed that 106 (100%) and 98 (92%) isolates of Eikenella corrodens were susceptible to amoxicillin and tetracycline, respectively. Twenty-three (68%) Prevotella intermedia isolates and 14 (67%) Prevotella nigrescens isolates were susceptible to amoxicillin. Seventy-nine percent of the P. intermedia isolates and 67% of the P. nigrescens isolates were susceptible to tetracycline. A higher percentage of β-lactamase-producing isolates of P. intermedia and P. nigrescens were identified with selective agar containing amoxicillin than with nonselective agar.